Groundwater Assessment and its Implication for Irrigation in Selected Coastal Areas of South-Western Nigeria - J.A, Adeyeye; O.D, Akinyemi; F.O, Akinluyi; M.O, Abiola; G. O, Badmus (Asian Journal of Agriculture and Rural Development, 2021)
Physicochemical and ionic characteristics of groundwater aquifers have been of tremendous importance in water applications. Groundwater in selected coastal communities (Badagry, Epe, Ikorodu, and Ilaje/ese-odo) of south-western Nigeria was assessed for domestic and irrigation suitability. One hundred and ninety-two (192) groundwater samples were obtained and analyzed for chemical composition and major ionic ratio over a period of four seasons using standard methods. Results indicated abundance of ions in the order HCO3– > Cl–> SO42– for anions, and K+ > Na+ > Ca2+> Mg2+ for cations. Piper's diagram revealed calcium (Ca2+) and magnesium (Mg2+) as the dominant cations, while sulphate and chloride were the dominant anions with a mixture of two major groundwater types: Ca–Cl water and mixed Ca–Mg–Cl. The presence of Ca–Cl facies water type suggests potential ion exchange (Na2+ with Ca2+) reaction in these coastal aquifers. Cation exchangeable values (CEV), and molar ratios of Mg/Ca, HCO3/Cl, and Na/Cl, showed high values (>1) across all locations indicating the occurrence of saline water ingression in groundwater samples, especially during the dry spell. The increasing K+, Na+, and Cl– characteristics of the groundwater and calculated ionic indices values indicated the influence of seawater intrusion. However, total hardness values showed that the samples were very soft in nature. Irrigation water quality suitability, as indicated by sodium adsorption ratio (SAR), permeability index (PI), and percentage sodium (PS) varied with seasons and location, showing that water will cause soil deterioration and poor crop performance if intensively used for irrigation without proper precautions.